Nuprl Lemma : respects-equality-quotient
∀[X,T:Type]. ∀[E1:X ⟶ X ⟶ ℙ]. ∀[E2:T ⟶ T ⟶ ℙ].
  (respects-equality(x,y:X//E1[x;y];x,y:T//E2[x;y])) supposing 
     ((∀x,y:X.  (E1[x;y] 
⇒ (x ∈ T) 
⇒ ((y ∈ T) ∧ E2[x;y]))) and 
     respects-equality(X;T) and 
     EquivRel(X;x,y.E1[x;y]) and 
     EquivRel(T;x,y.E2[x;y]))
Proof
Definitions occuring in Statement : 
equiv_rel: EquivRel(T;x,y.E[x; y])
, 
quotient: x,y:A//B[x; y]
, 
uimplies: b supposing a
, 
respects-equality: respects-equality(S;T)
, 
uall: ∀[x:A]. B[x]
, 
prop: ℙ
, 
so_apply: x[s1;s2]
, 
all: ∀x:A. B[x]
, 
implies: P 
⇒ Q
, 
and: P ∧ Q
, 
member: t ∈ T
, 
function: x:A ⟶ B[x]
, 
universe: Type
Definitions unfolded in proof : 
uall: ∀[x:A]. B[x]
, 
uimplies: b supposing a
, 
member: t ∈ T
, 
so_lambda: λ2x y.t[x; y]
, 
so_apply: x[s1;s2]
, 
sq_stable: SqStable(P)
, 
implies: P 
⇒ Q
, 
respects-equality: respects-equality(S;T)
, 
all: ∀x:A. B[x]
, 
squash: ↓T
, 
subtype_rel: A ⊆r B
, 
prop: ℙ
, 
and: P ∧ Q
, 
quotient: x,y:A//B[x; y]
, 
cand: A c∧ B
Lemmas referenced : 
sq_stable__respects-equality, 
quotient_wf, 
istype-base, 
subtype_rel_self, 
respects-equality_wf, 
equiv_rel_wf, 
istype-universe, 
quotient-member-eq
Rules used in proof : 
sqequalSubstitution, 
sqequalTransitivity, 
computationStep, 
sqequalReflexivity, 
Error :isect_memberFormation_alt, 
cut, 
introduction, 
extract_by_obid, 
sqequalHypSubstitution, 
isectElimination, 
thin, 
hypothesisEquality, 
sqequalRule, 
Error :lambdaEquality_alt, 
applyEquality, 
because_Cache, 
independent_isectElimination, 
hypothesis, 
independent_functionElimination, 
Error :lambdaFormation_alt, 
Error :equalityIstype, 
Error :universeIsType, 
sqequalBase, 
equalitySymmetry, 
imageMemberEquality, 
baseClosed, 
imageElimination, 
Error :functionIsType, 
instantiate, 
dependent_functionElimination, 
Error :productIsType, 
universeEquality, 
Error :inhabitedIsType, 
pertypeElimination, 
promote_hyp, 
productElimination, 
equalityTransitivity
Latex:
\mforall{}[X,T:Type].  \mforall{}[E1:X  {}\mrightarrow{}  X  {}\mrightarrow{}  \mBbbP{}].  \mforall{}[E2:T  {}\mrightarrow{}  T  {}\mrightarrow{}  \mBbbP{}].
    (respects-equality(x,y:X//E1[x;y];x,y:T//E2[x;y]))  supposing 
          ((\mforall{}x,y:X.    (E1[x;y]  {}\mRightarrow{}  (x  \mmember{}  T)  {}\mRightarrow{}  ((y  \mmember{}  T)  \mwedge{}  E2[x;y])))  and 
          respects-equality(X;T)  and 
          EquivRel(X;x,y.E1[x;y])  and 
          EquivRel(T;x,y.E2[x;y]))
Date html generated:
2019_06_20-PM-00_32_24
Last ObjectModification:
2018_11_29-PM-07_01_37
Theory : quot_1
Home
Index